Immunotherapy approaches to treat adult acute lymphoblastic leukemia. Issue 6 (2nd June 2016) - Maino, Elena; Bonifacio, Massimiliano; Scattolin, Anna Maria; Bassan, Renato
ABSTRACT: Recent developments in immunotherapy are improving treatment results of B-precursor acute lymphoblastic leukemia. This advancement is promoted by new monoclonal antibodies such as inotuzumab ozogamicin, ofatumumab and blinatumomab, by rituximab, and by genetically engineered chimeric antigen receptor-modified T-cells. These treatments, variously targeting CD22, CD20 and CD19 antigens, yield unprecedented high rates of hematologic and molecular remissions even when used in monotherapy and in chemo-resistant or post-transplantation relapsed patients. Beside the encouraging results in relapsed/refractory disease, these agents may open a totally new era in the frontline management of this illness, redefining treatment standards and options for different risk subsets and placing the achievement of a molecular remission at the forefront of treatment objectives. The ever increasing importance of modern immunotherapy in improving treatment design and therapeutic outcome is reviewed.